Yi-Zhi-Fang-Dai Formula Protects against Aβ 1–42 Oligomer Induced Cell Damage via Increasing Hsp70 and Grp78 Expression in SH-SY5Y Cells - Liu, Lumei (Hindawi Publishing Corporation, 2016)
Yi-Zhi-Fang-Dai formula (YZFDF) is an experiential prescription used to cure dementia cases like Alzheimer's disease (AD). In this study, the main effective compounds of YZFDF have been identified from this formula, and the neuroprotective effect against Aβ 1–42 oligomer of YZFDF has been tested in SH-SY5Y cells. Our results showed that YZFDF could increase cell viability and could attenuate endothelial reticula- (ER-) mediated apoptosis. Evidence indicated that protein folding and endothelial reticula stress (ERS) played an important role in the AD pathological mechanism. We further explored the expression of Hsp70, an important molecular chaperon facilitating the folding of other proteins, and Grp78, the marker protein of ERS in SH-SY5Y cells. Data told us that YZFDF pretreatment could influence the mRNA and protein expression of these two proteins. At last, we also found that YZFDF pretreatment could activate Akt in SH-SY5Y cells. All these above indicate that YZFDF could be a potent therapeutic candidate for AD treatment.